Robust Velocity Control for a Launch Vehicle Erection System - Saber, Ahmed K.; Maged, Shady A.; Abdelaziz, M.; Mohamed, Mostafa S. (Journal of Robotics and Control (JRC), 2025)
The design of a launch vehicle erection system requires careful consideration of factors such as load capacity, pressure requirements, actuator type, safety mechanisms, and control strategy. Ensuring precise velocity control is critical, as the system’s changing geometry and dynamic behavior influence its loading conditions, stability, and overall performance. This study investigates the velocity control of a hydraulic erection beam using a proportional directional control valve (PDCV). Four control techniques are examined: a classical PID controller, a sliding mode controller (SMC), a model predictive controller (MPC), and a PID controller optimized using the Particle Swarm Optimization (PSO) method. The controllers are evaluated through MATLAB/SIMULINK simulations under both undisturbed and disturbed conditions. Simulation results indicate that the classical PID controller struggles with stability under disturbances, while the MPC exhibits slow response times and fails to reach the desired position. The integration of PSO further degrades performance by introducing instability. In contrast, the SMC demonstrates superior robustness, achieving minimal response variation across all conditions. Comparative experiments validate these findings, confirming that SMC offers the best balance of precision, reliability, and disturbance rejection. These results highlight that SMC is the most effective control technique for real-world hydraulic erection systems, ensuring high stability, accuracy, and operational reliability.